BODY COMPOSITION AND MORTALITY IN PREVALENT HEMODIALYSIS PATIENTS: HEMO STUDY - Rebecca Filipowicz; Tom H. Greene; Guo Wei; Srinivasan Beddhu (The Korean Society of Nephrology, 2012)
Both higher body size (as indicated by body mass index- BMI) and higher muscle mass (as indicated by serum creatinine- (SCr)) are associated with better survival in HD patients (pts) but the relative importance of muscle vs. body size is not established. In the current study, the associations of SCr, BMI and the ratio of Scr to BMI with time to death were examined in Cox proportional hazards models using HEMO study data. Details of HEMO Study have been published elsewhere. In the current study, the associations of SCr, BMI and the ratio of Scr to BMI with time to death were examined in Cox proportional hazards models adjusted for age, gender, race, and HEMO trial interventions. Associations of SCr, BMI and SCr/BMI with mortality (n=1,775). Table 1 Model 1 HR (95% CI) For each change in SD of SCr 0.68 (0.63, 0.74) For each change in SD of BMI 0.86 (0.80, 0.93) Model 2 For each change in SD of SCr/BMI 0.82 (0.75, 0.89) The results indicate that patient differences in Scr level are substantially more strongly predictive of mortality thanpatient differences in BMI, relative to the SD of each factor. Furthermore, each SD increase in the ratio SCr/BMI wasassociated with 18% lower risk of death. In subgroup analyses, each SD increase in the SCr/ BMI ratio was associated with lower risk of death in those with BMI< 25 (HR 0.69, 95% CI 0.2-0.78), BMI 25-29.9 (HR 0.72, 95% CI 0.57 -0.90) and BMI 30 (HR 0.53, 95% CI 0.37-0.76). Both SCr and BMI are associated with lower risk of death in HD pts. However, in the HEMO Study, the magnitude of the association of SCr with mortality was stronger than the magnitude of the association of BMI with mortality, and higher SCr/BMI ratio was also associated with lower risk of death. Interventions targeting muscle mass at any level of BMI may improve survival in HD pts.